Breast Cancer: Learning about Radiation Therapy - Martha C. Monroe; Barbara F. Shea (EDIS)
FCS8835, a 3-page fact sheet by Martha C. Monroe and Barbara F. Shea, provides a basic orientation to external radiation therapy for the treatment of breast cancer. Published by the UF Department of Family Youth and Community Sciences, February 2010.